Analysis of the effect of variations in cutting speed and feed depth in the ST42 steel turning process on surface roughness - Saifuddin, Saifuddin; Sumardi, Sumardi; Faturrahman, Abdul (Journal of Mechanical Engineering and Fabrication, 2024)
The quality of the turning results, especially on the surface, is greatly influenced by three parameters, namely spindle speed, feed rate, and depth of cut. The level of surface flatness greatly affects the results of the workpiece after being processed on a lathe. Based on field experience, in the turning process, in order to obtain good surface flatness quality, good component selection is also required. The selection of components in question is one that has a significant effect on the results of the workpiece feed. The lathe tool is the main component in the machining process besides the lathe and the workpiece. The purpose of this study was to determine the surface roughness value of ST42 steel with variations in spindle rotation and cutting depth in the turning process. This test was carried out with a PL-1000 G model lathe with ST42 steel specimens. The roughness tester used was the Mitutoyo SJ-310. The results obtained were the best surface roughness value at 550 rpm spindle rotation of 3.925 µm at a depth of 0.2 mm. The best surface roughness value at 1020 rpm spindle speed is 3.258 µm at a depth of 0.2 mm. The best surface roughness value at 1800 rpm spindle speed is 1.551 µm at a cutting depth of 0.4 mm